ENHANCEMENT OF GIANT MAGNETORESISTANCE IN Fe2O3-MWCNT/PVA NANoCOMPOSITE FILM - S. Purwanto; Wisnu Ari Adi; Salim Mustofa (Jurnal Sains Materi Indonesia, 2015)
ENHANCEMENT OF GIANT MAGNETORESISTANCE IN Fe2O3-MWCNT/PVA NANoCOMPOSITE FILM. Synthesis and magnetic properties characterization of Fe2O3-MWCNT/PVA nano Composite film were carried out. Fe2O3-MWCNT as a filler of nano Composite thin film were synthesized using simple mixing methods froma solution containing FeCl3, and Multi-Walled Carbon Nanotube (MWNT). The solution was sonicated for almost 20 minutes then dried at 450 oC for one hour. The mixture of the two composition was dispersed with Sodium Dodecyl Sulfate (SDS) in 20 mL aquabidest and homogenized by ultrasonicator for 15 minutes at 40 oC. Then filler was then mixed with Polyvinyl Alcohol (PVA) with some various concentration and dried overnight at room temperature. X-Ray Diffraction (XRD) analysis and Raman Spectroscopy were used to find out the presence of Fe2O3 phase in as prepared sample. Iron oxide phase partially filled in the wall of MWCNT observed by Transmission Electron Microscope (TEM). The Giant Magnetoresistance (GMR) properties were investigated. The maximum GMR value was negative 80% of the composition 1:9 filler/matrix volume ratio. The linear negative of the magnetoresistance (MR) ratio is coincident with a model as proposed by Nguyen, Spivak and Shklovskii (NSS) and related to the effect of quantum interference between Fe2O3-MWCNT in PVA matrix.